Self-transcendent experiences as promoters of ecological wellbeing? Exploration of the evidence and hypotheses to be tested - Isham, Amy; Elf, Patrick; Jackson, Tim (Frontiers in Psychology, 2022)
In recent years, much has been written on the role of different mental states and their potential to influence our way of thinking and, perhaps more importantly, the way we act. With the recent acceleration of environmental and mental health issues, alongside the limited effectiveness of existing interventions, an exploration of new approaches to deliver transformative change is required. We therefore explore the emerging potential of a type of mental state known as Self-Transcendent Experiences (STEs) as a potential driver of ecological wellbeing. We focus on four types of STEs: those facilitated by experiences of flow, awe, and mindfulness, as well as by psychedelic-induced experiences. Some of these experiences can occur naturally, through sometimes unexpected encounters with nature or during immersion in every-day activities that one intrinsically enjoys, as well as through more intentional practices such as meditation or the administration of psychedelics in controlled, legal settings. We explore the evidence base linking each of the four types of STE to ecological wellbeing before proposing potential hypotheses to be tested to understand why STEs can have such beneficial effects. We end by looking at the factors that might need to be considered if STEs are going to be practically implemented as a means of achieving ecological wellbeing.